Manufacturing method of anti-dazzle low-flashing microcrystalline glass and anti-dazzle low-flashing microcrystalline glass
Patent Information
- Application Number
- CN202611204064.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-13
AI Technical Summary
该差异化蚀刻行为导致蚀刻后的微晶玻璃表面残留大量凸起的纳米级晶粒与微观凹凸结构,微观形貌不均匀性显著提升
[0017]根据上述技术方案,本发明通过设置第一深度大于第二深度,确保喷砂刻蚀承担主要的材料去除任务,而湿法抛光仅作为精修工序。这一设计大幅减少了氢氟酸的用量,降低了工艺的环保压力和安全风险,同时通过喷砂刻蚀能够对微晶玻璃两相实现同步刻蚀,有效改善了传统纯湿法蚀刻中因非晶相优先腐蚀所导致的闪点、发黄和水波纹等表观缺陷。
Smart Images

Figure CN122897604A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of manufacturing anti-glare and low-flicker microcrystalline glass, specifically, to a method for manufacturing anti-glare and low-flicker microcrystalline glass and the anti-glare and low-flicker microcrystalline glass itself. Background Technology
[0002] Glass-ceramics, also known as microcrystalline glass, are inorganic non-metallic materials composed of a composite of crystalline and amorphous phases. Compared to traditional single-amorphous materials such as soda-lime silicate glass and high-alumina silicate glass, microcrystalline glass, with its unique composite structure of crystalline and amorphous phases, exhibits significant comprehensive advantages in mechanical strength, bending toughness, thermal stability, and resistance to chemical corrosion. Based on these superior mechanical properties, microcrystalline glass has been widely used in consumer electronics and optical window fields such as smartphones, digital cameras, smart wearable devices, and automotive displays. As a core substrate for screens and body protective covers, it possesses extremely high market application value and widespread adoption.
[0003] With the increasing demands for display quality in applications such as automotive displays and high-end consumer electronics, screen cover glass not only needs excellent mechanical protection properties but also good optical performance. Among these, anti-glare glass, or AG glass cover glass, has attracted much attention due to its ability to effectively reduce ambient light reflection and improve visibility in strong light environments. Currently, the preparation of anti-glare microcrystalline glass mainly employs a wet etching process, using hydrofluoric acid (HF) or its mixed acid system to chemically etch the glass surface. This etching creates a microscopic uneven structure on the glass surface, achieving diffuse reflection of light and thus achieving an anti-glare effect. A typical existing process flow is: glass substrate treatment → coating layer → photoresist coating → exposure and development → film layer etching → photoresist removal → wet etching → film layer removal → wet polishing.
[0004] However, the aforementioned manufacturing process is cumbersome and costly. Traditional anti-glare glass manufacturing processes require two steps: coating a film and applying photoresist to the glass surface. The coating process typically employs magnetron sputtering, which consumes high-purity metal or oxide targets, high-purity process gases, and has a very high energy consumption rate, making it a costly step that hinders the industry's large-scale development.
[0005] Meanwhile, the two-phase structure of glass-ceramics also leads to severe etching defects and optical malfunctions. Glass-ceramics contain both continuous amorphous glass phases and dispersed crystalline phases, which differ significantly in chemical activity. Under the action of a hydrofluoric acid-based etching system, the more chemically active continuous amorphous glass phase is preferentially etched and stripped away, gradually hollowing out the matrix structure between the crystalline phases; while the more corrosion-resistant grains are etched later, and only after the glass phase matrix encapsulating the grains is completely eroded will the exposed crystalline grains be slowly etched. This differentiated etching behavior results in a large number of protruding nanoscale grains and microscopic uneven structures remaining on the surface of the etched glass-ceramics, significantly increasing the inhomogeneity of the microstructure. These densely exposed nanocrystals cause irregular diffuse reflection, scattering, and refraction of incident light, ultimately causing severe appearance defects such as severe flashing (strong screen flicker), yellowing, uneven light transmission, and water ripple-like light and shadow defects, seriously affecting display quality. Summary of the Invention
[0006] The purpose of this invention is to provide a method for manufacturing anti-glare and low-flicker microcrystalline glass. This method achieves synergistic etching of the crystalline and amorphous phases of the microcrystalline glass through a composite etching system of sandblasting and wet polishing, which significantly improves the optical performance and appearance quality of the product. At the same time, sandblasting replaces part of the acid etching process, which greatly reduces the amount of hazardous chemical reagents such as hydrofluoric acid.
[0007] To achieve the above objectives, the present invention provides a method for manufacturing anti-glare, low-flicker microcrystalline glass, comprising: S1. Apply a protective film to the surface of the glass substrate; S2. Expose and develop the protective film to form a patterned protective film on its surface; S3. The glass substrate obtained in S2 is subjected to sandblasting etching, and the sandblasting etching depth is the first depth. S4. Remove the patterned protective film from the surface of the glass substrate; S5. Perform wet polishing on the glass substrate obtained in S4, and etch to the second depth. The patterned protective film exposes the location of the recesses on the surface of the glass substrate; The first depth is greater than the second depth.
[0008] Preferably, the first depth is 2-15 μm.
[0009] Preferably, the second depth is 2-5 μm.
[0010] Preferably, in step S3, the abrasive material used for sandblasting is 800-2000 mesh, the sandblasting pressure is 0.15–0.4 MPa, and the sandblasting angle is 45°-75°.
[0011] Preferably, in step S5, wet polishing is performed using an acidic solution.
[0012] Preferably, in step S5, the wet polishing is performed using an alkaline solution.
[0013] Preferably, in step S5, wet polishing etching is performed until the haze reaches 30%.
[0014] The present invention also provides an anti-glare and low-flicker microcrystalline glass, wherein one side of the anti-glare and low-flicker microcrystalline glass is configured as an anti-glare and low-flicker functional surface containing microstructures, and the microstructures are arranged in a periodic, non-periodic, or quasi-periodic arrangement along the anti-glare and low-flicker functional surface. The bottom of the microstructure is concave to form a hole, and the top surface forms a protrusion. The surface shape of the hole or protrusion can be spherical, aspherical, or free-form. The concave and convex sidewalls form a continuous and smooth curved surface. The inner surface of the concave hole is covered with a small number of nano-sized protrusions, which are dome-shaped or rhomboid-shaped.
[0015] Preferably, the diameter of the circumcircle of the projection of the microstructure onto the anti-glare and low-flicker functional surface is 1-150 μm.
[0016] Preferably, the height of the recess or protrusion is 1µm-80µm.
[0017] According to the above technical solution, this invention ensures that sandblasting etching undertakes the main material removal task by setting the first depth to be greater than the second depth, while wet polishing is only used as a finishing process. This design significantly reduces the amount of hydrofluoric acid used, lowers the environmental pressure and safety risks of the process, and at the same time, sandblasting etching can achieve simultaneous etching of both phases of the microcrystalline glass, effectively improving the surface defects such as flash point, yellowing, and water ripples caused by the preferential corrosion of amorphous phases in traditional pure wet etching.
[0018] Therefore, this manufacturing method achieves synergistic etching of the crystalline and amorphous phases of microcrystalline glass through a composite etching system of sandblasting and wet polishing, significantly improving the optical performance and appearance quality of the product. At the same time, sandblasting replaces part of the acid etching process, greatly reducing the amount of hazardous chemical reagents such as hydrofluoric acid, and improving the safety and environmental friendliness of the process. Moreover, patterned protection is achieved through coating and exposure development, which can precisely control the position and distribution of the recesses, ensuring the consistency and repeatability of the product.
[0019] Other features and advantages of the present invention will be described in detail in the following detailed description section. Attached Figure Description
[0020] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used together with the following detailed description to explain the invention, but do not constitute a limitation thereof. In the drawings: Figure 1 This is a flowchart of a manufacturing method for anti-glare, low-flicker microcrystalline glass; Figure 2 This is a schematic diagram of the structure of an anti-glare, low-flicker microcrystalline glass manufactured using a manufacturing method for anti-glare, low-flicker microcrystalline glass. Figure 3 This is a schematic diagram of the structure of a microcrystalline glass manufactured using the method of Comparative Example 1; Figure 4 These are schematic diagrams of the 3D morphology of the glass-ceramics obtained in Example 1 and Comparative Example 1. Figure 5 This is a schematic diagram of the appearance of the microcrystalline glass obtained in Example 1 and Comparative Example 1.
[0021] Explanation of reference numerals in the attached figures 10. Glass substrate; 1. Microstructure; 11. Concave holes; 12. Protrusions; 3-nanometer-scale protrusions. Detailed Implementation
[0022] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.
[0023] In this invention, unless otherwise stated, directional terms included in the terminology represent only the orientation of the term in its normal use or as commonly understood by those skilled in the art, and should not be regarded as a limitation on the term.
[0024] See Figure 1 The method for manufacturing an anti-glare, low-flicker microcrystalline glass includes: S1. A protective film is applied to the surface of the glass substrate 10; The glass substrate 10 is a microcrystalline glass substrate with a thickness of 0.1mm-2.0mm. Before lamination, the glass substrate 10 is pre-treated: the microcrystalline glass substrate is pre-cleaned with deionized water. During the cleaning process, a soft brush or ultrasonic cleaning method can be used to remove surface dust and organic contaminants. If there is oil on the board surface, a special cleaning agent or organic solvent can be added for degreasing and oil removal.
[0025] The film material used for lamination is a photosensitive film layer, which is an exposeable and developable film layer, such as dry film DFR, PCB liquid photosensitive wet film, etc. The lamination process must be carried out in a photolithography workshop. One of the following two lamination methods can be used: Spray coating method: The photosensitive film layer is sprayed onto the surface of the glass substrate 10 with a coating thickness of 10-100um. After spraying, the drying temperature is 20-150℃ and the time is 1-30min.
[0026] Lamination method: The photosensitive film layer is laminated onto the surface of the glass substrate 10 using a lamination machine. The lamination temperature is 20-150℃, the time is 1-30min, and the lamination pressure is 0.2-0.8MPa.
[0027] Through the coating process, a uniform protective film is formed on the surface of the glass substrate 10, providing a mask basis for subsequent pattern transfer and selective etching.
[0028] S2. Expose and develop the protective film to form a patterned protective film on its surface; The exposure energy is controlled between 50-500 mJ / cm², and the exposure wavelength needs to be optimally selected based on the product application scenario and the spectral photosensitivity characteristics of the photosensitive film layer to ensure accurate replication of the mask pattern. The development process uses a specific type and concentration of developer to complete the pattern development operation, achieving accurate transfer of the mask pattern to the photosensitive film layer.
[0029] After the exposure and development processes are completed, the glass substrate 10 is washed with deionized water and dried in a temperature range of 50-300℃.
[0030] After exposure and development, a patterned protective film is formed on the protective film. The patterned protective film covers the area on the surface of the glass substrate 10 that needs to be protected, while exposing the positions on the surface of the glass substrate 10 where the recesses 11 to be formed will be. The pattern of the patterned protective film can be set as periodic, non-periodic, or quasi-periodic voids according to design requirements, and the overall outline of the planar projection can be designed as a honeycomb structure, quasi-lattice structure, etc.
[0031] S3. The glass substrate 10 obtained in S2 is subjected to sandblasting etching, and the sandblasting etching depth is the first depth. A sandblasting etching process is employed to etch the exposed glass substrate 10 surface—the area not protected by the patterned protective film. The abrasive material used for sandblasting can be selected from one or more materials such as white fused alumina, silicon carbide, glass microspheres, brown fused alumina, and garnet sand. During the sandblasting etching process, high-speed abrasive particles bombard the exposed glass substrate 10 surface, simultaneously and indiscriminately etching both the crystalline and amorphous phases of the glass-ceramic glass through physical impact. This physical etching process controls the differential dissolution degree between the crystalline and amorphous phases in subsequent chemical etching, effectively reducing the absolute height of the crystalline phase protrusions. After sandblasting etching, a preliminary recessed structure is formed in the exposed area of the glass substrate 10 surface, achieving pre-etching of the recessed holes.
[0032] S4. Remove the patterned protective film from the surface of the glass substrate 10; The patterned protective film is removed using a wet chemical method. The optimal process time is determined based on the residual adhesive layer thickness, curing degree, and material characteristics of the glass substrate 10 to ensure complete removal of the photosensitive material without damaging the functional pattern on the substrate. The overall removal process time is controlled between 1 and 15 minutes. After film removal, the exposed area of the glass substrate 10 has formed a recessed structure of the first depth, while the area originally covered by the protective film remains in its original planar state.
[0033] In one embodiment, sodium bicarbonate or a sodium carbonate solution is used to remove the patterned protective film.
[0034] S5. The glass substrate 10 obtained in S4 is wet polished, and the etching depth is the second depth. The patterned protective film exposes the location of the recesses 11 on the surface of the glass substrate 10; The first depth is greater than the second depth.
[0035] The glass substrate 10 is wet-polished and etched using an acidic solution, which is a hydrofluoric acid solution system. The etching depth of the wet polishing is a second depth, which is less than the first depth.
[0036] During wet polishing, hydrofluoric acid isotropically etches the surface of the glass substrate 10. Since the sandblasting etching in step S3 has already created preliminary depressions in the exposed area, wet polishing further rounds off the sharp burrs and edges left by the sandblasting, forming a smooth-transition concave structure. Simultaneously, because the sandblasting etching has pre-cut both the crystalline and amorphous phases simultaneously, the preferential dissolution of the amorphous phase by hydrofluoric acid during the wet polishing stage is limited to a shallower area, effectively avoiding the protrusion of a large number of nanoscale grains.
[0037] During the wet polishing stage, the shape of the recessed sidewalls obtained by sandblasting and etching is polished into a smooth surface, and the depth of the recess is also increased to a certain extent. As the size of the upper surface of the recess expands to form a recessed hole 11, the spacing between the recessed structures that were originally divided by the flat surface is reduced and eventually connected to each other, forming a protrusion 12 at the connection position.
[0038] By setting the first depth to be greater than the second depth, sandblasting etching is ensured to handle the primary material removal task, while wet polishing serves only as a finishing process. This design significantly reduces the amount of hydrofluoric acid used, lowering the environmental impact and safety risks of the process. Simultaneously, sandblasting etching enables simultaneous etching of both phases of the microcrystalline glass, effectively improving surface defects such as flash points, yellowing, and water ripples caused by preferential corrosion of the amorphous phase in traditional pure wet etching.
[0039] Therefore, this manufacturing method achieves synergistic etching of the crystalline and amorphous phases of microcrystalline glass through a composite etching system of sandblasting and wet polishing, significantly improving the optical performance and appearance quality of the product. At the same time, sandblasting replaces part of the acid etching process, greatly reducing the amount of hazardous chemical reagents such as hydrofluoric acid, and improving the safety and environmental friendliness of the process. Moreover, patterned protection is achieved through film coating and exposure development, which can precisely control the position and distribution of the recesses 11, ensuring the consistency and repeatability of the product.
[0040] In this embodiment, preferably, the first depth is 2-15 μm.
[0041] In step S3, the sandblasting etching depth is controlled within the range of 2-15 μm. This depth range is selected based on the following considerations: if the first depth is less than 2 μm, the pretreatment effect of sandblasting etching is insufficient, and it cannot effectively level the height difference between the crystalline phase and the amorphous phase of the microcrystalline glass. After subsequent wet polishing, nanoscale grain protrusions may still appear, affecting the flash point and appearance quality; if the first depth is greater than 15 μm, the sandblasting etching is too intense, which may cause excessive damage to the surface of the glass substrate 10, affecting the mechanical strength of the substrate, and increasing the difficulty and time of subsequent wet polishing.
[0042] Under the condition of a first depth of 2-15um, sandblasting etching can effectively remove the material in the exposed area of the glass substrate 10 surface, forming a preliminary recessed structure of moderate depth, providing a good precursor morphology for subsequent wet polishing.
[0043] Therefore, controlling the first depth to 2-15um ensures that the sandblasting etching can simultaneously and fully etch both phases of the glass-ceramic, while avoiding damage to the mechanical properties of the substrate from excessive etching, thus achieving a balance between etching effect and substrate strength.
[0044] In this embodiment, preferably, the second depth is 2-5 μm.
[0045] In the wet polishing step S5, the etching depth of the acidic solution on the surface of the glass substrate 10, i.e., the second depth, is controlled within the range of 2-5 μm. The second depth is less than the first depth, thereby ensuring that sandblasting etching undertakes the main material removal task, and wet polishing is only used as a finishing process.
[0046] If the second depth is less than 2 μm, wet polishing is insufficient to correct the sharp burrs and edges remaining on the surface after sandblasting and etching. The sidewalls of microstructure 1 are difficult to form a smooth and continuous curved transition, affecting the anti-glare effect and image clarity. If the second depth is greater than 5 μm, it means that the amount of hydrofluoric acid etching increases. On the one hand, excessive etching of the amorphous phase may cause the nanoscale grain protrusions to re-emerge. On the other hand, it will also increase the consumption of hydrofluoric acid.
[0047] Under the condition of a second depth of 2-5 μm, wet polishing can effectively remove the damaged layer and sharp burrs on the surface after sandblasting and etching, so that the sidewall of the concave hole 11 forms a smooth and continuous curved surface transition without obvious edges. At the same time, the inner surface of the concave hole 11 retains only a small number of nano-scale protrusions 3 with a dome-shaped or rhomboid peak shape, thereby ensuring that the flash point value is at a low level and the appearance is colorless while achieving a good anti-glare effect.
[0048] In this embodiment, preferably, in step S3, the abrasive material used for sandblasting is 800-2000 mesh, the sandblasting pressure is 0.15-0.4MPa, and the sandblasting angle is 45°-75°.
[0049] In step S3, the sandblasting etching process uses an abrasive material with a mesh size of 800-2000. The choice of abrasive mesh size affects the fineness of the etching: the higher the mesh size, the finer the abrasive particles, and the smoother the etched surface; the lower the mesh size, the coarser the abrasive particles, and the higher the etching efficiency. The 800-2000 mesh range can balance etching efficiency and surface quality.
[0050] The sandblasting pressure should be controlled between 0.15 and 0.4 MPa. If the pressure is too low, the etching efficiency will be insufficient, making it difficult to achieve the required first depth; if the pressure is too high, it may cause excessive damage to the surface of the glass substrate 10, affecting the substrate strength and subsequent processing.
[0051] The sandblasting angle is controlled between 45° and 75°. Within this angle range, the abrasive particles can bombard the surface of the glass substrate 10 at an appropriate impact angle, which ensures etching efficiency while avoiding deep pit damage that may be caused by vertical impact and scratches that may be caused by horizontal impact.
[0052] The abrasive material can be selected from one or more of the following materials: white fused alumina, silicon carbide, glass microspheres, brown fused alumina, garnet sand, etc.
[0053] In this embodiment, preferably, in step S5, wet polishing is performed using an acidic solution.
[0054] In this embodiment, preferably, in step S5, wet polishing is performed using an alkaline solution.
[0055] In the wet polishing step S5, an acidic solution is used to polish and etch the glass substrate 10. The acidic solution is a hydrofluoric acid solution system.
[0056] The main functions of wet polishing include: (1) chemically etching the sharp burrs and edges remaining on the surface after sandblasting and etching, making them round and smooth; (2) refining the recessed structure formed by sandblasting and etching, forming a concave hole 11 with a spherical, non-spherical or free-form surface shape; (3) through isotropic chemical etching, making the sidewall of the concave hole 11 have a continuous and smooth curved transition without obvious edges.
[0057] The etching depth of wet polishing is less than the first depth of sandblasting etching, thus significantly reducing the amount of etching compared to traditional processes. Simultaneously, the amount of hydrofluoric acid used in wet polishing is also significantly reduced compared to traditional pure wet etching processes. Therefore, using an acidic solution for wet polishing allows for precise chemical shaping of the sandblasted surface, forming smooth and rounded concave hole structures 11, achieving excellent anti-glare effects; at the same time, it effectively avoids the generation of a large number of nanoscale protrusions 3.
[0058] In this embodiment, preferably, in step S5, wet polishing etching is performed until the haze reaches 30%.
[0059] In the wet polishing process of step S5, the haze value is used as the process control endpoint. Haze refers to the percentage of transmitted light flux scattered when light passes through the material to the total transmitted light flux. Wet polishing is stopped when the haze value reaches 30%.
[0060] A haze of 30% is an experimentally verified performance balance point. At this haze value, the micro-uneven structure on the surface of the glass substrate 10 has appropriate roughness, which can effectively scatter ambient light to achieve an anti-glare effect, while avoiding excessive scattering that would cause blurred edges of screen pixels or exacerbate flickering.
[0061] In actual production, the haze value on the surface of the glass substrate 10 can be monitored in real time by a haze meter. When the reading reaches 30%, polishing is stopped immediately, for example, by removing the glass substrate 10 from the acid solution or neutralizing the acid solution, thereby achieving precise process control based on optical performance as the criterion.
[0062] By setting 30% haze as the endpoint for wet polishing, the optimal balance between anti-glare effect and display clarity is achieved, ensuring the consistency and repeatability of the product's optical performance.
[0063] This invention also provides, for example Figure 2 The anti-glare and low-flicker microcrystalline glass has one side configured as an anti-glare and low-flicker functional surface containing microstructure 1. The microstructure 1 is arranged in a periodic, non-periodic, or quasi-periodic arrangement along the anti-glare and low-flicker functional surface. The bottom of the microstructure 1 is recessed inward to form a concave hole 11, and the top surface forms a protrusion 12. The surface shape of the concave hole 11 or the protrusion 12 is spherical, non-spherical or free-form. The sidewalls of the concave hole 11 and the protrusion 12 are continuous and smooth curved surfaces. A small number of nano-sized protrusions 3 are distributed on the inner surface of the concave hole 11. The nano-sized protrusions 3 are dome-shaped or rhomboid pointed.
[0064] The anti-glare, low-flicker microcrystalline glass includes a glass substrate 10 and an anti-glare, low-flicker functional surface disposed on one side of the glass substrate 10. The glass substrate 10 is a microcrystalline glass substrate with a thickness of 0.1 mm to 2.0 mm.
[0065] Multiple microstructures 1 are arranged on the anti-glare and low-flicker functional surface. The arrangement of the microstructures 1 along the anti-glare and low-flicker functional surface can be periodic, non-periodic, or quasi-periodic, and the overall outline of the planar projection can be designed as a honeycomb configuration, a quasi-lattice configuration, etc.
[0066] Microstructure 1 is specifically manifested as a concave hole 11 or a protrusion 12. The concave hole 11 is a structure formed by the inward indentation of the bottom of microstructure 1, and the protrusion 12 is a protruding structure formed on the top surface of microstructure 1. The surface shape of the concave hole 11 or the protrusion 12 can be spherical, aspherical, or free-form. The sidewalls of the concave hole 11 and the protrusion 12 form a continuous and smooth curved transition without obvious edges.
[0067] On the inner surface of the recess 11, a small number of nano-sized protrusions 3 are further distributed. These nano-sized protrusions 3 have a dome-shaped or rhomboid-shaped morphology. The nano-sized protrusions 3 originate from the incompletely etched crystalline phase particles in the glass-ceramic, but due to the combined treatment of sandblasting and wet polishing, their number is controlled to a very low level, and their morphology is rounded, so they will not have a significant adverse effect on optical performance.
[0068] This anti-glare, low-flicker microcrystalline glass achieves excellent anti-glare performance by setting an anti-glare, low-flicker functional surface containing microstructure 1; the surface shape of the concave hole 11 or the protrusion 12 is spherical, aspherical or free-form surface with smooth transition of sidewalls, ensuring controllable scattering of light; the inner surface of the concave hole 11 has only a small number of nano-scale protrusions 3 with rounded shape, avoiding the optical defects caused by a large number of sharp grain protrusions in traditional pure wet etching, and achieving a good appearance with low flash point and no discoloration.
[0069] In this embodiment, preferably, the diameter of the circumcircle of the projection of the microstructure 1 onto the anti-glare and low-flicker functional surface is 1-150 μm.
[0070] The projection shape of microstructure 1 on the anti-glare and low-flicker functional surface can be quadrilateral, pentagon, or polygonal. The diameter of the circumcircle of the projection of microstructure 1 is controlled within the range of 1µm-150µm.
[0071] The lower limit of the circumscribed circle diameter, 1µm, ensures that the microstructure 1 has sufficient size to produce an effective scattering effect; the upper limit of 150µm avoids the microstructure 1 becoming too large, which would result in pixel visibility or a decrease in display clarity. Within this size range, the microstructure 1 can effectively scatter ambient light to achieve an anti-glare effect without affecting the display clarity of the screen.
[0072] The side length of the projection of microstructure 1 onto the anti-glare and low-flicker functional surface ranges from 0.1µm to 100µm.
[0073] Therefore, by controlling the diameter of the projection circumcircle of microstructure 1 within 1-150um, it is ensured that microstructure 1 has an appropriate size to achieve excellent anti-glare effect, while avoiding affecting display clarity or causing visible pixel distortion due to excessive size.
[0074] In this embodiment, preferably, the height of the concave hole 11 or the protrusion 12 is 1um-80um.
[0075] The depth of the recess 11 is the vertical distance from the bottom of the recess 11 to the anti-glare and low-flicker functional surface, and the height of the protrusion 12 is the vertical distance from the top of the protrusion 12 to the anti-glare and low-flicker functional surface. The lower limit of 1 μm for the height of the recess 11 or the protrusion 12 ensures that the microstructure 1 has sufficient undulation amplitude to produce an effective scattering effect; the upper limit of 80 μm avoids the decrease in mechanical strength and the degradation of optical performance caused by the microstructure 1 being too high or too deep.
[0076] In actual products, the specific height of the recess 11 or the protrusion 12 can be optimized according to the target haze value and flash point value. Controlling the height of the recess 11 or the protrusion 12 to 1um-80um ensures that the microstructure 1 has sufficient undulation amplitude to achieve an effective anti-glare effect, while avoiding the adverse effects of excessive undulation on the mechanical strength and optical clarity of the substrate.
[0077] Comparative Example 1 The microcrystalline glass substrate was cleaned with a neutral cleaning agent for 5 minutes to remove surface dust and organic contaminants.
[0078] Then, a metal or oxide film layer is deposited on the glass surface using a magnetron sputtering coating process. Subsequently, photoresist is applied to the glass surface using a machine, and the pattern is transferred onto the photoresist through exposure and development.
[0079] A patterned protective film is obtained on the surface of the glass substrate 10 by etching the metal or oxide film layer that is not protected by photoresist using a specific etching solution, and then removing the photoresist by spraying.
[0080] The patterned protective film was used to perform wet etching on the parts not protected by the film, with an etching depth of 2-3 μm.
[0081] The patterned protective film is then removed using a film etching solution.
[0082] Finally, polish again with an acidic solution until the haze on the haze meter is 30%.
[0083] Testing revealed that the product obtained in this comparative study had a yellow, water-ripple appearance, a flash point of 3.47 on a 140ppi screen, a DOI of 0, and surface roughness Ra of 0.371um and Rz of 1.573um.
[0084] Comparative Example 2 The microcrystalline glass substrate was cleaned with a neutral cleaning agent for 5 minutes to remove surface dust and organic contaminants.
[0085] The photosensitive film layer is laminated onto the surface of the microcrystalline glass by lamination, and the drying temperature is 150℃ for 30 minutes. Then, the pattern is transferred onto the photosensitive film layer by exposure and development to obtain a patterned protective film.
[0086] The portion of the glass substrate 10 not protected by the patterned protective film was wet-etched using an acidic solution etching process, with an etching depth of 2-3 μm.
[0087] Then, a specific film-removing solution is used to spray and remove the protective film.
[0088] After removing the protective film, an acidic solution is used for etching and polishing until the haze instrument shows a haze of 30%.
[0089] Testing revealed that the product prepared in this comparative example has a yellow, water-ripple appearance, a flash point of 1.41 on a 140ppi screen, a DOI of 0, and surface roughness Ra of 0.358um and Rz of 1.878um.
[0090] Comparative Example 3 The soda-lime glass substrate was cleaned with a neutral cleaning agent for 5 minutes to remove surface dust and organic contaminants.
[0091] A photosensitive film layer is laminated onto the surface of soda-lime glass using a lamination method. The film is dried at 150°C for 30 minutes. Subsequently, the pattern is transferred onto the photosensitive film layer through exposure and development to obtain a patterned protective film.
[0092] The unpatterned protective film is etched using a sandblasting etching process, with a sandblasting etching depth of 2-3 μm.
[0093] The patterned protective film was removed by spraying with a sodium bicarbonate solution.
[0094] An acidic solution was used to etch and polish the glass substrate 10 with the patterned protective film removed until the haze was 30% as indicated by a haze meter.
[0095] Finally, the soda-lime glass was polished using a sandblasting polishing process for 20 seconds.
[0096] Testing revealed that the product prepared in this comparative example had no color difference, a flash point of 1.06 on a 140ppi screen, a DOI of 29.4, and surface roughness Ra of 0.329um and Rz of 1.637um.
[0097] Example 1 The microcrystalline glass substrate was cleaned with a neutral cleaning agent for 5 minutes to remove surface dust and organic contaminants.
[0098] Then, a film was applied to the surface of the glass substrate 10 by spraying, and the photosensitive film layer was sprayed onto the surface of the microcrystalline glass. The drying temperature was 150℃ and the time was 30 minutes.
[0099] The pattern is transferred to the photosensitive film layer by exposure and development to form a patterned protective film, exposing the position of the recess 11 to be formed on the surface of the glass substrate 10.
[0100] A sandblasting etching process is used to etch the parts of the glass substrate 10 that are not protected by the patterned protective film, with a sandblasting etching depth of 2-3 μm.
[0101] The patterned protective film on the surface of the glass substrate 10 is removed by spraying sodium bicarbonate solution.
[0102] The glass substrate 10 was etched and polished using an acidic solution until the haze level was 30% as indicated by a haze meter.
[0103] Testing showed that the anti-glare, low-flicker microcrystalline glass prepared in this embodiment had no color difference, a flash point of 1.21 on a 140ppi screen, a DOI of 27.4, and surface roughness Ra of 0.317um and Rz of 1.851um.
[0104] Example 2 The manufacturing steps in this embodiment are similar to those in Embodiment 1. The only difference is that an alkaline solution is used instead of an acidic solution to etch and polish the glass substrate 10 until the haze instrument shows a haze of 30%.
[0105] Testing showed that the anti-glare, low-flicker microcrystalline glass prepared in this embodiment had no discoloration, a flash point of 1.18 on a 140ppi screen, a DOI of 21.3, and surface roughness Ra of 0.303um and Rz of 1.665um.
[0106] The experimental results are shown in Table 1.
[0107] Table 1:
[0108] The comparison data above shows that: 1) Comparing Example 1 and Example 2, in the wet etching step, the glass substrate 10 manufactured using alkaline solution or acidic solution has no appearance problems, but the glass substrate 10 etched using alkaline solution has better flash point and anti-glare effect.
[0109] 2) Comparing Examples 1 and 2 with Comparative Example 3, it was found that the microcrystalline glass products obtained after processing the microcrystalline glass using the manufacturing method of anti-glare low-flicker microcrystalline glass have reached a flash point similar to that of ordinary soda-lime glass.
[0110] 3) Comparing Examples 1 and 2 with Comparative Examples 1 and 2, the flash point and appearance of the glass-ceramic are improved after using the manufacturing method of the anti-glare low-flicker glass-ceramic. This is because sandblasting etching can simultaneously etch the amorphous phase and crystalline phase of the glass-ceramic, thereby improving the flash point and appearance.
[0111] Third, the comparison of Examples 1-2 and Comparative Examples 1 and 2 shows that the scheme involving sandblasting etching significantly improves the flash point and appearance of the glass-ceramic. This is because sandblasting etching can simultaneously etch both the amorphous and crystalline phases of the glass-ceramic, thereby effectively improving the flash point and appearance defects.
[0112] The preferred embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited to the specific details of the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.
[0113] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
[0114] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.
Claims
1. A method for manufacturing an anti-glare, low-flicker microcrystalline glass, characterized in that, include: S1. A protective film is applied to the surface of the glass substrate (10); S2. Expose and develop the protective film to form a patterned protective film on the surface of the protective film; S3. The glass substrate (10) obtained in S2 is subjected to sandblasting etching, and the sandblasting etching depth is the first depth. S4. Remove the patterned protective film from the surface of the glass substrate (10); S5. The glass substrate (10) obtained in S4 is wet polished, and the etching depth is the second depth. The patterned protective film exposes the location of the recesses (11) on the surface of the glass substrate (10); The first depth is greater than the second depth.
2. The method for manufacturing anti-glare, low-flicker microcrystalline glass according to claim 1, characterized in that, The first depth is 2-15um.
3. The method for manufacturing anti-glare, low-flicker microcrystalline glass according to claim 1, characterized in that, The second depth is 2-5 μm.
4. The method for manufacturing anti-glare, low-flicker microcrystalline glass according to claim 1, characterized in that, In step S3, the abrasive material used for sandblasting is 800-2000 mesh, the sandblasting pressure is 0.15-0.4MPa, and the sandblasting angle is 45°-75°.
5. The method for manufacturing anti-glare, low-flicker microcrystalline glass according to claim 1, characterized in that, In step S5, the wet polishing is performed using an acidic solution.
6. The method for manufacturing anti-glare, low-flicker microcrystalline glass according to claim 1, characterized in that, In step S5, the wet polishing is performed using an alkaline solution.
7. The method for manufacturing anti-glare, low-flicker microcrystalline glass according to claim 1, characterized in that, In step S5, the wet polishing etching is performed until the haze reaches 30%.
8. An anti-glare, low-flicker microcrystalline glass, characterized in that, One side of the anti-glare and low-flicker microcrystalline glass is configured as an anti-glare and low-flicker functional surface containing microstructures (1), and the microstructures (1) are arranged in a periodic, non-periodic, or quasi-periodic manner along the anti-glare and low-flicker functional surface. The microstructure (1) has an inwardly recessed hole (11) at the bottom and a protrusion (12) on the top surface. The surface of the hole (11) or the protrusion (12) is spherical, non-spherical or free-form. The sidewalls of the concave hole (11) and the protrusion (12) form a continuous smooth curved surface. A small number of nano-sized protrusions (3) are distributed on the inner surface of the concave hole (11). The nano-sized protrusions (3) are dome-shaped or rhomboid-shaped.
9. The anti-glare, low-flicker microcrystalline glass according to claim 8, characterized in that, The diameter of the circumcircle of the projection of the microstructure (1) onto the anti-glare and low-flicker functional surface is 1-150 μm.
10. The anti-glare, low-flicker microcrystalline glass according to claim 8, characterized in that, The height of the concave hole (11) or protrusion (12) is 1um-80um.